Nonlocal Telegraph Equation in Frame of the Conformable Time-Fractional Derivative. (3rd March 2019) - Bouaouid, Mohamed; Hilal, Khalid; Melliani, Said
Abstract : We use the cosine family of linear operators to prove the existence, uniqueness, and stability of the integral solution of a nonlocal telegraph equation in frame of the conformable time-fractional derivative. Moreover, we give its implicit fundamental solution in terms of the classical trigonometric functions.